PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA KOPERASI JASA TRI CAPITAL INVESTAMA - Purnamasari, Dewi; Utari, Woro (Prodi Magister Manajemen Universitas Wijaya Putra, 2024)
This study aims to analyze leadership style, compensation, employee performance, work motivation in Jasa Cooperative Tri Capital Investama Regional East Java 1 Bali Nusra, to test and analyze the effect of transformational leadership style and compensation on employee performance Cooperative Services Tri Capital Investama East Java Regional 1 Bali Nusra with work motivation as an intervening variable. The population in the study included all employees, totaling 56 people and the sample in this study were 56 employees of the Tri Capital Investama Jasa Cooperative, East Java Regional 1 Bali Nusra, using a census technique. The data that has been obtained is then analyzed using a partial least square – structural inquiry model (PLS-SEM). The results showed that the transformational leadership style, compensation, employee performance, and employee motivation of the Tri Capital Investama Jasa Cooperative East Java 1 Bali Nusra Region were in the high category, the transformational leadership style had a significant effect on employee performance through employee work motivation in the Tri Capital Investama service cooperative. Compensation has no significant effect on employee performance through employee motivation in the Tri Capital Investama service cooperative.